(untitled) (Praxis Educativa, 2020)
There has been an increase in enrollment in higher educationas a result of educational democratization.Consequently, university admission criteria have been affected. However, in Argentina, where national public universities are completely free, graduation rates have not shown increases proportional to those observed in enrollment. Thus, the aim of the study was to compare the educational trajectory of two cohorts of students of an Argentine national university based on the characteristics of their admission: eliminatory (traditional examination modality) or unrestricted (without exam). A probabilistic sample of 445 students was used: 198 of the students entered through the traditional examination modality (2014) and 245 entered through the unrestricted modality (2015). The results indicate a divergence in educational trajectories, with higher performance indicators for the 2014 cohort. The findings represent a contribution to the study of the democratization policies of higher education.